Please stand by: how oncolytic viruses impact bystander cells. (8th August 2018) - Sprague, Leslee; Braidwood, Lynne; Conner, Joe; Cassady, Kevin A; Benencia, Fabian; Cripe, Timothy P
Oncolytic viruses (OVs) do more than simply infect and kill host cells. The accepted mechanism of action for OVs consists of a primary lytic phase and a subsequent antitumor and antiviral immune response. However, not all cells are subject to the direct effects of OV therapy, and it is becoming clear that OVs can also impact uninfected cells in the periphery. This review discusses the effects of OVs on uninfected neighboring cells, so-called bystander effects, and implications for OV therapies alone or in combination with other standard of care chemotherapy.